On-Foot Hyperlocal Delivery - An Overview, Challenges, and Opportunities: Case Studies in Korea - Yahya, Bernardo Nugroho (Institute of Research and Community Outreach - Petra Christian University, 2020)
During the Covid19 pandemic, many local business were struggling to survive. With the rising of click and collect solutions, business strives to survive by offering pick-up points and maintaining the social distance policy. The demand for goods and services of customers are met instantly from the local offline shops via digital platform. Meanwhile, local businesses in a specific geographical area are still striving from the hard times due to least popularity and competitivenes in the services such as delivery. Hyperlocal delivery comes into the logistics industry to meet the issues from local businesses. While the hyperlocal delivery terminology is still new, there have been some real world practices. This study attempts to define the hyperlocal delivery and explore multiple case studies to analyze the on-foot delivery as a rising of quick commerce in the gig economy. The multiple case studies will take place on the hyperlocal delivery business models in South Korea. The overview of the hyperlocal “on-foot” delivery will be described in four dimension of analysis; strategy, customer, cost-revenue, and process model. At the end, some research challenges and opportunities are presented to show how the research communities can contribute to the field